Expansion of Clinical and Genetic Spectrum of DDX3X Neurodevelopmental Disorder in 23 Chinese Patients - Dai, Yuwei; Yang, Zhuanyi; Guo, Jialing; Li, Haoyu; Gong, Jiaoe; Xie, Yuanyuan; Xiao, Bo; Wang, Hua; Long, Lili (Frontiers in Molecular Neuroscience, 2022)
Aim: De novo DDX3X variants account for 1-3% of unexplained intellectual disability cases in females and very rarely in males. Yet, the clinical and genetic features of DDX3X-neurodevelopmental disorder in Chinese cohort have not been characterized. Method: 23 Chinese patients (22 females and 1 male) with 22 de novo DDX3X deleterious variants were detected among the 2317 probands with unexplained intellectual disability (ID) undertaking whole exome sequencing (WES). The age, sex, genetic data, feeding situation, growth, developmental conditions, auxiliary examinations of the cohort were collected. The Chinese version of Gesell Development Diagnosis Scale (GDDS-C) was used to evaluate neurodevelopment of DDX3X patients. The Social Communication Questionnaire (SCQ)-Lifetime version was applied as a primary screener to assess risk for Autism spectrum disorder (ASD). Result: 17 DDX3X variants were novel and 22 were de novo. Missense variants overall were only slightly more common than loss-of-function variants and were mainly located in two functional subdomains. The average age of this cohort was 2.67 (±1.42) years old. Overlapping phenotypic spectrum between this cohort and previously described reports includes intellectual disability (23/23,100%) with varying degrees of severity, muscle tone abnormalities (17/23,73.9%), feeding difficulties (13/23,56.5%), ophthalmologic problems (11/23,47.8%) and seizures (6/23,26.1%). 15 individuals had notable brain anatomic disruption (15/23, 65.2%), including lateral ventricle enlargement, corpus callosum abnormalities and delayed myelination. 9 patients showed abnormal electroencephalogram results (9/23, 39.1%). Hypothyroidism was firstly noted as a novel clinical feature (6/23,26.1%). The five primary neurodevelopmental domains of GDDS-C in 21 patients impaired severely, and 13 individuals were above the “at-risk” threshold for ASD. Interpretation: Although a certain degree of phenotypic overlap with previously reported cohorts, our study described the phenotypic and variation spectrum of 23 additional individuals carrying DDX3X variants in Chinese population, adding hypothyroidism as a novel finding. We confirmed the importance of DDX3X as a pathogenic gene in unexplained intellectual disability, supporting the necessity of application of WES in patients with unexplained intellectual disability.